2003
DOI: 10.1002/cem.800
|View full text |Cite
|
Sign up to set email alerts
|

Statistical process monitoring: basics and beyond

Abstract: This paper provides an overview and analysis of statistical process monitoring methods for fault detection, identification and reconstruction. Several fault detection indices in the literature are analyzed and unified. Fault reconstruction for both sensor and process faults is presented which extends the traditional missing value replacement method. Fault diagnosis methods that have appeared recently are reviewed. The reconstruction-based approach and the contribution-based approach are analyzed and compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
164
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,340 publications
(169 citation statements)
references
References 73 publications
0
164
0
5
Order By: Relevance
“…They further gave a rule that the statistic less than one is considered normal. It has been suggested that the use of a single index is preferable in practice (Joe Qin, 2003).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…They further gave a rule that the statistic less than one is considered normal. It has been suggested that the use of a single index is preferable in practice (Joe Qin, 2003).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…The PCA is a well-established multivariate statistic model which projects standardized data into two orthogonal subspaces so as to reduce the dimensions of the data (Joe Qin, 2003). As it plays an important part in the proposed PCA-KSVM model, a brief introduction is given below for a reader convenience.…”
Section: A Principal Component Analysis (Pca)mentioning
confidence: 99%
“…If the correlation matrix of X is R where R=X¢X/(M-1), the singular value decomposition of R can be represented as (Joe Qin, 2003),…”
Section: A Principal Component Analysis (Pca)mentioning
confidence: 99%
“…Therefore, the scalar thresholds can qualify the process status. The approximated control limits of T 2 and Q statistics, with a confidence level α, can be determined from the normal operating data in several ways by applying the probability distribution assumptions (Kourti and MacGregor, 1995;Qin, 2003). The control limits can be calculated as follows:…”
Section: Preliminaries Of Pcamentioning
confidence: 99%
“…Multivariate statistical methods, such as principal component analysis (PCA) and partial least squares (PLS), are widely used in industry for process monitoring (Nomikos and MacGregor, 1995;Qin, 2003;Ge and Song, 2008;Garcia-Alvarez et al, 2012). Other complementary multivariate statistical process monitoring methods, including canonical variate analysis, kernel PCA, dynamic PCA, and independent component analysis, have been proposed to address the limitations of PCA-or PLSbased monitoring strategies (Russell et al, 2000;Juricek et al, 2004;Lee et al, 2004a;2006).…”
Section: Introductionmentioning
confidence: 99%